Closure of non-healing perianal Crohn’s disease with surgery and vacuum-assisted closure (VAC) system - Orhan Uzun; Mürşit Dinçer; Aziz Serkan Senger; Kamuran Cumhur Değer; Mustafa Duman (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Uzun O, Dinçer M, Senger AS, Değer KC, Duman M. Closure of non-healing perianal Crohn’s disease with surgery and vacuum-assisted closure (VAC) system. Turk J Gastroenterol 2018; 29: 367-9.